2022
DOI: 10.1002/cncr.34574
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure in pediatric medulloblastoma and implications for hippocampal sparing

Abstract: Background Hippocampal avoidance (HA) has been shown to preserve cognitive function in adult patients with cancer treated with whole‐brain radiation therapy for brain metastases. However, the feasibility of HA in pediatric patients with brain tumors has not been explored because of concerns of increased risk of relapse in the peri‐hippocampal region. Our aim was to determine patterns of recurrence and incidence of peri‐hippocampal relapse in pediatric patients with medulloblastoma (MB). Methods and materials W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We read with great interest the recently published article entitled "Patterns of failure in pediatric medulloblastoma and implications for hippocampal sparing" by Baliga et al 1 The study provides valuable insights into the patterns of failure in pediatric medulloblastoma, a common type of brain tumor that affects children. The authors also revealed that hippocampal-avoidance (HA) volumetric-modulated arc therapy and HA intensity-modulated proton therapy techniques to reduce dose to the hippocampus are dosimetrically feasible.…”
Section: Is the Hippocampus-sparing Attempt Really Reasonable Within ...mentioning
confidence: 99%
“…We read with great interest the recently published article entitled "Patterns of failure in pediatric medulloblastoma and implications for hippocampal sparing" by Baliga et al 1 The study provides valuable insights into the patterns of failure in pediatric medulloblastoma, a common type of brain tumor that affects children. The authors also revealed that hippocampal-avoidance (HA) volumetric-modulated arc therapy and HA intensity-modulated proton therapy techniques to reduce dose to the hippocampus are dosimetrically feasible.…”
Section: Is the Hippocampus-sparing Attempt Really Reasonable Within ...mentioning
confidence: 99%
“…Some toxicity types, for instance, those related to endocrine and neurocognitive functions, are unavoidable in the CSI phase of the treatment since the pituitary gland and brain are integral parts of the CTV. Consequently, sparing is only possible in the boost phase, although innovative ideas, such as hippocampal sparing CSI, have been investigated [ 1 , 2 , 3 ]. Due to its physical characteristics, the traditionally used megavoltage photon beam allows for only limited improvements in CSI-related toxicity reduction, even considering the high-technology advances in photon radiotherapy in recent decades [ 4 ].…”
Section: Introductionmentioning
confidence: 99%